(3GdEYdGe HJGQjN Cgd GdGSdGe GdEYdGe HhajGJ GdEYdGes - (3Jbi GdOjf CHi HcQ Hf CMeO Hf eMeO Hf YeQ Hf eMeOs; (3GHf GdeLGhQ , jhSa Hf jYbhH Hf eMeO Hf Ydj GdTjHGfj GdOeTbj, LeGd GdOjf CHh GdaJM,J (B690 (3g` s
(3ChdgG (B:s
(3ai GdeMQe OQS GdTjN Jbi GdOjfYhVkG Yf GdTjN JGL GdOjf GdeQGcTi GdYQV ajgG s
(3BNQgG (B:s
(3dGjTOO Ydjge ai GdJbGVi hChUi ai eQV ehJg HKdK eGdg hOaf ai JQHI CHjg HGdUMg ef fGMjI GdTQcSjg Je GdeLdO GdKGfi s
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B258 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B345s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B51 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B22 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs